Inhibitors of receptor-mediated endocytosis block the entry of Bacillus anthracis adenylate cyclase toxin but not that of Bordetella pertussis adenylate cyclase toxin. - Gordon, V M (1988)
Bordetella pertussis and Bacillus anthracis produce extracytoplasmic adenylate cyclase toxins (AC toxins) with shared features including activation by calmodulin and the ability to enter target cells and catalyze intracellular cyclic AMP (cAMP) production from host ATP. The two AC toxins were evaluated for sensitivities to a series of inhibitors of known uptake mechanisms. Cytochalasin D, an inhibitor of microfilament function, abrogated the cAMP response to B. anthracis AC toxin (93%) but not the cAMP response elicited by B. pertussis AC toxin. B. anthracis-mediated intoxication of CHO cells was completely inhibited by ammonium chloride (30 mM) and chloroquine (0.1 mM), whereas the cAMP accumulation produced by B. pertussis AC toxin remained unchanged. The block of target cell intoxication by cytochalasin D could be bypassed when cells were first treated with anthrax AC toxin and then exposed to an acidic medium. These data indicate that despite enzymatic similarities, these two AC toxins intoxicate target cells by different mechanisms, with anthrax AC toxin entering by means of receptor-mediated endocytosis into acidic compartments and B. pertussis AC toxin using a separate, and as yet undefined, mechanism.